2017
DOI: 10.1080/08952841.2017.1413830
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationship between walking activity and sleep disturbance among community-dwelling older adult with diabetes in Taiwan

Abstract: This study explored the gender differences in the relationship between walking activity and sleep disturbances. A cross-sectional study of 201 community-dwelling older adults with diabetes was conducted in southern Taiwan. Using the Taiwanese version of the International Physical Activity Questionnaire, self-administered short version (IPAQ-SS), information on physical activity and sleep disturbance conditions was collected. Among older female adults with diabetes, 54.2% reported sleep disturbance significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Studies have suggested sex differences in symptoms experience [40][41][42]. We found that sex was the strongest predictor of high symptom burden.…”
Section: Discussionmentioning
confidence: 48%
“…Studies have suggested sex differences in symptoms experience [40][41][42]. We found that sex was the strongest predictor of high symptom burden.…”
Section: Discussionmentioning
confidence: 48%
“…external factors, and physical activity barriers of patients with type II DM, and design patient-centered physical activity programs such as: resistance exercises performed in three sets of 8 to 12 repetitions for three times per week (Hsieh et al, 2018), daily walking for at least 30 min (Cheng et al, 2019), and Tai Chi exercise three times per week with each session lasting up to 1 hr (Chen et al, 2010). This type of exercise will help these patients to improve sleep problems and physical fitness in order to manage diabetes and facilitate quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Videoconferencing-delivered group-based physical activity (Jeske et al, 2020), physical therapist-guided resistance training (Hsieh et al, 2018), home-based exercise (Chen et al, 2010), and simple ways to exercise (daily walking) (Cheng et al, 2019) help to overcome time and transportation issues and facilitate motivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adan, Fabbri, Natale, and Prat (2006) and Larcher, Benhamou, Pépin, and Borel (2015) indicated that sleep hygiene-sleep facilitating and inhibiting practices-is related to sleep quality and sleep duration. In addition, Cheng et al (2017) described that physical activity is associated with sleep disturbance. Although sleep patterns, sleep hygiene and physical activities can be antecedents of sleep disturbance in people without diabetes, they can also have a considerable impact on the sleep quality and sleep duration of people with diabetes.…”
Section: Letter Regarding "Sleep Disturbance In People With Diabetes:mentioning
confidence: 99%